2020
DOI: 10.34234/ded.655916
|View full text |Cite
|
Sign up to set email alerts
|

Etkili Vatandaşlık Eğitiminde Değerler Eğitimi: Sosyal Bilgiler Öğretmenlerinin Düşünceleri

Abstract: Bu makale, en az iki hakem tarafından incelendi ve intihal içermediği teyit edildi. / This article has been reviewed by at least two referees and scanned via a plagiarism software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…In their study with prospective teachers, Deveci and Selanik Ay (2014) determined that the participants considered social studies as a course that facilitates life in citizen education and provides social order. Karasu Avcı et al (2020) found that social studies teachers thought that social studies course adds value to students and raises effective citizens. In the present study, it was concluded that the social studies teachers were of the opinion that the content suitable for citizenship education should be used while providing citizenship education in the social studies course.…”
Section: Discussionmentioning
confidence: 99%
“…In their study with prospective teachers, Deveci and Selanik Ay (2014) determined that the participants considered social studies as a course that facilitates life in citizen education and provides social order. Karasu Avcı et al (2020) found that social studies teachers thought that social studies course adds value to students and raises effective citizens. In the present study, it was concluded that the social studies teachers were of the opinion that the content suitable for citizenship education should be used while providing citizenship education in the social studies course.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies on educational administrators, teachers and preservice teachers. It is seen that mostly values education studies are conducted on teachers (Bayırlı et al, 2020;Ergin & Karataş, 2014;Karasu Avcı et al, 2020;Sayın, 2020;Kuzu, 2015;Karamustafaoğlu & Amanat, 2017;Batmaz & Erdoğan, 2019;Erbaş & Başkurt, 2020;Aktepe et al, 2020;İbret, Karatekin, & Avcı, 2015). Some studies are about administrators and teachers (Vatansever Bayraktar & Karakülçe, 2019;Yazar et al, 2017;Karakülçe, 2018;Gürhan, 2017;Yediyıldız, 2019); some studies are about candidate teachers (Kurtdede Fidan, 2016;Kıral & Dinçer, 2018).…”
Section: Journal Of Qualitative Research In Education Eğitimde Nitel ...mentioning
confidence: 99%
“…Ayrıca vatanseverlik değerinin toplumda da önemli bir yansıması vardır. Veliler ve öğretmenler üzerinde yapılan çalışmalar vatanseverlik değerinin en fazla önemsenen değerlerden olduğunu göstermektedir (Beldağ, Özdemir ve Nalçacı, 2017;Karasu-Avcı, Faiz ve Turan, 2020;Yıldırım, Becerikli ve Demirel, 2017). Schwartz ve diğerlerinin (2012) değer sınıflandırmasına göre Türkiye 5. sınıf sosyal bilgiler öğretim programı kazanımlarının üst değerler bağlamında sıralaması; muhafazakarlık, kendini geliştirme/değişime açıklık ve öz-aşkınlık şeklindedir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified